A SCALE DEVELOPMENT TO DETERMINE UNIVERSITY STUDENTS' ATTITUDES TO ONLINE EXAMS ASSESSMENT - KORHAN ARUN; Nesli Kahraman Gedik; Zeynep Olcay; Guven Ozdemir; mustafa Çıkrıkçı (Novìtnâ Osvìta, 2023)
Purpose: This study aims to develop and validate a scale to determine university students' attitudes toward assessment and evaluation in online exams. Background: Measuring students' attitudes toward online exams is crucial, especially in the context of emergency transitions to online learning and the impact of external factors such as the COVID-19 pandemic. Students' perspectives on online examination practices in higher education institutions are significant in understanding students' attitudes and perceptions of online exams for effective implementation. Method: During the developmental phase of the scale, 13 items were created and presented for expert opinion. The scale propositions are designed to question the compliance of the courses with the curricula in the online education process, the transparency of online exams, and the University's technological infrastructure for online exams. The participants in the study consist of 1095 students studying in different programs at the Vocational Schools of three foundation universities in Istanbul, and they were reached via e-mail. Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted. Findings: The results obtained prove that the 13-question scale is valid and reliable and is a good measurement to determine university students' attitudes to online exams. Implications for Research and Practice: Attitudes are likely determinants of academic achievement. Furthermore, utilizing e-tests positively impacts higher education students' performance and participation in online testing. Therefore, it is essential to consider students' attitudes towards online exams to increase academic success in online courses and provide better learning outcomes. Thus, scale development plays a pivotal role in advancing knowledge within specific domains of social science research, and it is integral to ensuring the quality and reliability of online exam instruments used in higher education.